POTRET NILAI-NILAI KEARIFAN LOKAL DI BALIK PRAKTIK AKUNTANSI OLEH PEDAGANG TAKJIL - Thalib, Mohamad Anwar; Mohamad, Anggun Fitra N.; Ijini, Amelia; Ibahim, Khairunnisa (RISTANSI: Riset Akuntansi, 2023)
The objective of this study is to portray the cultural values inherent in the accounting practices of takjil traders. Employing an Islamic paradigm with an Islamic ethnomethodology approach, the research reveals three accounting practices: firstly, capital accounting based on the values of mutual assistance, known locally among the Gorontalo people as huyula, sharing, and gratitude.